Monitoring of Radioactive Background in Qlyasan Stream, Tanjero River and Derbendikhan Lake in Sulaimani Governorate/Kurdistan Region-Iraq. - Khwakaram, Ahmed I. (Sulaimani Journal for Pure and Applied Sciences, 2017)
The study aimed to assess the background radiation and to calculate the annual effective dose of Qlyasan stream, Tanjero River and Derbendikhan Lake in Sulaimani Governorate. Although Qlyasan stream and Tanjero River were used intensively for irrigation purposes, they also used as sink for receiving a large volume of domestic and industrial wastewater without any treatment. Consequently, this may be led to different types of contamination such as radiation. Therefore the background radiation was measured at nine sites along Qlyasan stream, Tanjero River and after the confluence Point of Tanjero River by Derbendikhan Lake. The measurements were carried out in two periods, namely May and June 2015, by using a PRM-9000 Mazur nuclear radiation monitor instrument. The average background radiation of effective dose at destination sites was ranged from 0.07 to 0.08 µSvhr-1 in May, but in June, ranged from 0.06 to 0.10 µSv hr-1. The calculated average of the annual accumulated effective dose was varied between 0.105-0.175 mSv y-1, this finding was within the recommended permissible limit by the International Commission on Radiological Protection (ICRP) and (UNSCEAR). The highest average of annual accumulated effective dose was 0.175 mSv y-1 and measured at site S3of Qlyasan stream.
Keywords: Derbendikhan Lake; Tanjero River; Qlyasan Stream; Background radiation; Annual Effective Dose